2005
DOI: 10.1680/geot.2005.55.2.143
|View full text |Cite
|
Sign up to set email alerts
|

A generic approach to soil–structure interaction considering the effects of soil heterogeneity

Abstract: The longitudinal variation of soil properties has a major influence for many types of structure, including pavements, buried pipes, raft foundations and railways, as it induces stresses and/or displacements that cannot be predicted when assuming soil homogeneity. A set of simple numerical models has been developed to describe how soil–structure interaction can be influenced by soil variability. These models include: (a) a description of the soil spatial variability, within the frame of geostatistics, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…This is consistent with the tendency observed in previous stochastic studies of foundations on randomly heterogeneous saturated soils (e.g. Fenton & Griffiths, 2002Breysse et al, 2005). The fact that the P 50 attains its maximum value at an intermediate rather than an extreme value of Ł(˜p à 0 ) is also intuitive, as ä s should approach zero when Ł(˜p à 0 ) approaches either zero or infinity.…”
Section: Rainfall-induced Differential Settlements Of Foundationssupporting
confidence: 90%
“…This is consistent with the tendency observed in previous stochastic studies of foundations on randomly heterogeneous saturated soils (e.g. Fenton & Griffiths, 2002Breysse et al, 2005). The fact that the P 50 attains its maximum value at an intermediate rather than an extreme value of Ł(˜p à 0 ) is also intuitive, as ä s should approach zero when Ł(˜p à 0 ) approaches either zero or infinity.…”
Section: Rainfall-induced Differential Settlements Of Foundationssupporting
confidence: 90%
“…The behaviors of the observed sample means and variances are fairly complicated. The phenomenon of the critical SOF reported in Fenton and Griffiths [3], Breysse et al [4], and Soubra et al [5] is observed for scenarios CI-SExp, SI-SExp, and CA-SExp  the sample means are minimal at   10m. This critical  is roughly equal to the width of the soil specimen, which is also roughly equal to the length of the slip curve.…”
Section: Complicated Behaviors Of the Mobilized Shear Strengthmentioning
confidence: 76%
“…Figure 9(a) shows the results for the four SExp scenarios, and Fig. 9 [4], and Soubra et al [5], where it is shown that more complex mechanisms can appear when the SOF is comparable to some multiple of the characteristic length of the structure (e.g., height of slope, diameter of tunnel, depth of excavation). Hence, spatial variability affects geotechnical analysis in a manner that is more fundamental than variance reduction.…”
Section: Complicated Behaviors Of the Mobilized Shear Strengthmentioning
confidence: 87%
See 1 more Smart Citation
“…Elachachi et al [3,4] considered the effect of soil-structure interaction on embedded pipe networks. Studies on soil-structure interaction considering the effects of soil heterogeneity have been presented by Breysse et al [5]. The results showed the effect of soil variability on the induced forces in linear mechanical systems.…”
Section: Introductionmentioning
confidence: 99%